Recent Applications and Advances of Migrating Birds Optimization - Kouka, Shaimaa; Makhadmeh, Sharif Naser; Al-Betar, Mohammed Azmi; Dalbah, Lamees Mohammad; Nachouki, Mirna (Archives of computational methods in engineering, 2024)
In this paper, the recent applications and advances of Migrating Birds Optimization (MBO) algorithm are reviewed. The MBO originated from the V flight shape of the migrating birds in nature to reduce the air pressure and increase the swarm speed. Although MBO is relatively unknown, it has been successfully applied for a plethora of optimization problems in many research fields, such as scheduling, manufacturing, communication and networking, etc. This is due to its impressive characteristics, such as easy-to-use, simple, adaptable and flexible, and sound and complete. Therefore, the growth of MBO is exponentially increased. This review paper considers the changes in the MBO structure, the growth, the foundation and inspiration, the applications, and the limitations. The review ends up with theoretical conclusions about MBO and the possible future directions to cope with the current revolutions in the exponential age.